A COMPARATIVE CLINICAL STUDY ON PATRA PINDA SWEDA AND NADI SWEDA IN THE PAIN MANAGEMENT OF GRIDHRASI W.S.R. TO SCIATICA (International Journal of Ayurveda and Pharma Research, 2019)
Gridhrasi as mentioned in Ayurveda explains a disorder where in pain starts from Sphik pradesha and radiates downwards to Kati, Prusta, Uru, Janu, Jangha and Pada, Due to this, the patient is unable to walk properly. Gridhrasi can be compared with Sciatica. Sciatica is a relatively common condition with a life time incidence varying from 13% to 40%. The corresponding annual incidence of an episode of Sciatica ranges from 1 to 5%. The incidence of Sciatica is related to age. It is rarely seen before the age of 20. Incidence peaks in fifth decade declines thereafter.Snehana and Swedana are considered as a general line of treatment for Vata Vyadhi which can be taken as a line of treatment for Gridhrasi also. Patra pinda Sweda (Vatashamak) and Nadi sweda (Vata Kapha shamak) is one such treatment modality comes under Snehana and Swedana is known for relieving the symptoms. Murchita Tila Taila due to its Vata Shamaka has been taken for the Sthanik abhyanga.30 patients of Gridhrasi were randomly selected and divided into 2 groups. Group A: 15 patients received Patra pinda sweda and Group B: 15 patients received Nadi sweda up to Samyak Swinna lakshana. Overall assessment of both groups, out of 30 patients, 2 (6.67%) got complete remission, 13 (43.34%) patients got marked response, 6 (20%) patients got moderate response and 9 patients got mild response.